(untitled) - Guell, Robert C. (Boston, 2010)
Developed to allow instructors the maximum flexibility to teach this material in a manner that fits their personal style, this edition covers events and topics such as: the housing bubble, the recession of 2007-2009, federal spending, poverty in the United States versus other developed countries, the environment, and foreign exchange rates.
Keywords: Economics,Kinh tế học